Dynamics of Properties of Laser Beams for Surface Hardening of Metals and Enrichment of Uranium and Transuranic Elements (Review) - Zavoiko , A.S. (Physics and Chemistry of Solid State, 2015)
In this article considered consequence scientific achievement in laser technology which carry out in last time,and actual in development electron trreat equipment material analisis basic position warmth model evaporation and condensation film, sphere be form. Discass and analisis problem pass wave interaction and absorb energetic impuls situation, powerful condition on emition characteristics concentration source in they manyfoton ionisation and complex connection for the tecnology regim, and kreterial laser obtaind. This problem developed practical making gas,solution dipping with obtaind new composite tipe will continue of protective coating based on metals with new mechanical and physical-chemical process of need in laser technology.